Combination of soil application and seed treatment formulations of Trichoderma species for integrated management of wet root rot caused by Rhizoctonia solani in chickpea (Cicer arietinum ) - DUBEY, S C; TRIPATHI, ARADHIKA; SINGH, BIRENDRA (The Indian Journal of Agricultural Sciences, 2012)
The efficacy of seed dressing and soil application formulations developed from the isolates of Trichoderma viride (IARI P1; MTCC 5369), T. virens (IARI P3; MTCC 5370) and T. harzianum (IARI P4; MTCC 5371) was evaluated individually and in combinations under pot and field experiments during the winter seasons of 2005–06, 2006–07 and 2007–08 for the management of wet root rot caused by Rhizoctonia solani Kühn and improvement in the yield of chickpea. Under pot experiments, T. virens based seed dressing formulation, viz. Pusa 5SD and soil application formulations, viz Pusa Biopellet 16G (PBP 16G) and Pusa Biogranule 6 (PBG 6) were found to be superior to other formulations in reducing wet root rot incidence and increasing the seed germination, shoot and root lengths in chickpea. Under field experiments, a combination of soil application of PBP 16G (T. virens) and seed treatment with either a combination of Pusa 5SD (T. virens) and carboxin or Pusa 5SD (T. virens) alone was superior to any of these formulations individually in increasing the seed germination, shoot and root lengths and grain yield and reducing the wet root rot incidence in chickpea. Seed treatment was more effective than soil application for all the parameters. Both soil application and seed treatment formulations enhanced the growth of the plants indicating growth promoting ability of the isolates used for development of the formulations. The efficacy of the formulations evaluated for the first time against wet root rot of chickpea.